IMPACT OF NET PROFIT MARGIN AND EARNING PER SHARE TO STOCK PRICE IN INDONESIAN BANKING LISTED COMPANY FROM 2019-2023 - Very; Pananda Pasaribu; Budi Kurniawan (Faculty of Economics and Business Universitas Pelita Harapan, 2025)
The banking sector plays a crucial role in Indonesia's economy, influencing stock market dynamics through key financial metrics. This study explores the impact of Net Profit Margin (NPM) and Earnings Per Share (EPS) on stock prices of Indonesian publicly listed banks during the 2019–2023 period. Using a quantitative approach, the research analyzed historical financial data and applied multiple linear regression techniques. Findings reveal that while NPM negatively affects stock prices, EPS demonstrates a significant positive influence, underscoring its importance as a key profitability indicator for investors. The results suggest a relationship between financial performance and stock valuation in the banking sector. These insights highlight the need for managers to balance operational efficiency with shareholder expectations, enhancing understanding of stock price determinants in sector-specific contexts.